Интеллектуальная система памяти с секционированными модулями на ПЛИС и кольцевыми шинами - Палагин, А.В.; Боюн, В.П.; Яковлев, Ю.С. (Управляющие системы и машины, 2017)
Предложена оригинальная структурная схема интеллектуальной системы памяти с секционированными модулями на ПЛИС с интефейсом PCI-Express и кольцевыми шинами, обеспечивающая масштабирование и повышение производительности системы в целом путем распараллеливания и реализации фрагментов алгоритма или подпрограмм пользовательской задачи одновременно несколькими или всеми секциями. Запропоновано оригінальну структурну схему інтелектуальної системи пам'яті з секционованими модулями на ПЛІС з интефейсом PCІ-Express, та кільцевими шинами, що забезпечує масштабування та підвищення продуктивності системи у цілому шляхом розпаралелювання і реалізації фрагментів алгоритму або підпрограм користувацького завдання одночасно декількома або всіма секціями. The aim. The original block diagram of intellectual memory system with the partitioned modules on FPGA with PCIExpress interface and the ring-bus circuits is offered, which provides scaling and increasing system productivity in whole by parallelizing and implementing the fragments of algorithm or subroutines of the user problem simultaneously by several or all sections. The concepts. Thus application of ring-bus circuits as well as application of FPGA, already on its own account in comparison with the traditional approaches of the memory systems construction, increase system productivity at the expense of some technological limitations through placing of ring-bus circuits on a chip, information consolidation in certain quanta of time for ring-bus circuits, etc., and also through hardware realization of the adequate mapping of algorithm of a solved problem on FPGA in parallel to the programme realization of the same algorithm. In addition, FPGA can be used for both information storage and information processing. Conclusion. Already these factors allow to conclude that, through application of N of the partitioned modules of memory on FPGA containing ring-bus circuits, the productivity of such system increases approximately in N times through paralleling of the user problem. The important factor is also that, besides traditional operations of the information record, storage and deliveries, the means of the information processing are situated here in immediate proximity, endowing memory system with properties of intellectuality, which also affects the productivity of such system and the area of its application.